Introduction: Symbolism and Politics - Gill, Graeme (Politics, religion & ideology, 2018)
Symbols are central features of organized human life, helping to define perception, shaping the way we view the world and understand what goes on within it. But, despite this key role in shaping understanding, there is never a single interpretation of a symbol that everyone within the community will accept, and the way in which symbols can mobilize antagonistic political factions demonstrates that they are as much a central element for power struggles as they are avenues to facilitate processes of identification. This dual potential is the object of discussion in the papers in this special issue, which sheds new lights on the understanding of the political function of symbols in a historical period characterized by volatile electoral behaviour, fragmented societies in search of collective identifications and growingly polarizing political models.